(untitled) (Chittagong University Journal of Biological Sciences, 2013)
Major physico-chemical properties of mango orchard soils (Mangifera indica L.) in different sites of three hill districts, Rangamati, Khagrachari and Bandarban were evaluated. Soils were sandy loam in texture at all the sites except foot hill soil of Shapchari. Soil pH, organic matter, total N and available P varied from 4.76 to 5.58, 1.43 to 2.49 %, 0.10 to 0.16 %, 0.86 mg kg-1 to 2.69 mg kg-1 soil, respectively in surface soil of different sites of mango orchard. 1N NH4OAc extractable K+, Ca2+ and Mg2+ ranged from 0.35 to 0.82, 2.50 to 3.66 and 0.60 to 1.57 cmol kg-1 of soils. Soil pH, organic matter, total N and available P varied significantly among the slope positions within the sites. Similar results were found in case of 1N NH4OAc extractable K+, Ca2+ and Mg2+. The soils are generally poor in organic matter and nutrients. DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17244 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):187-197, 2011